Preservation of soil resources which were destroyed as a result of military operations by means of land management - Dorosh, O.; Dorosh, Y.; Fomenko, V. (Land Management, Cadastre and Land Monitoring, 2023)
It is proved that soil protection has become a national environmental problem, so the contradictions between socio-economic needs of people and environmental safety requirements must be overcome. The existence of standards for the qualitative state of soils and their maximum permissible pollution in the legislative field indicates that they reflect only the chemical nature of anthropogenic loads, but there are no standards at all for such types of loads as physical, mechanical, reclamation and man-made, which is of particular importance in the context of military operations in Ukraine. It is substantiated that when assessing the level of damaged land and soil as a result of hostilities and determining the degree of suitability for their further use, it is necessary to take into account: the level of damage to the land plot as a percentage of its area; the degree of suitability; characteristics of contaminated land; proposals for further use of the land plot and measures to reduce the level of pollutants entering the soil. It is also proposed to implement measures to protect land and soil by means of land management through the development of appropriate land management documentation. Given the anthropogenic load on soils due to the impact of hostilities, the need to develop a working land management project for the reclamation of disturbed lands as a result of hostilities and a working land management project for the conservation of degraded, unproductive and technogenically polluted lands has been proved, which requires amendments to the Resolution of the Cabinet of Ministers of Ukraine of February 2, 2022, No. 86 "On Approval of the Rules for Developing Working Land Management Projects".Key words: soils, impact of military operations, anthropogenic footprint, soil conservation agriculture, land reclamation, land management
Keywords: soils; impact of military operations; anthropogenic footprint; soil conservation agriculture; land reclamation; land management